The effect of inflation, interest rates, and usd exchange on the indonesian sharia stock index (ISSI) Period 2019-2022 - Imam Al Amin; Muhammad Sholahuddin (Trigin Publisher, 2023)
Establishing an Islamic capital market is necessary in Indonesia as an Islamic country, one of which is the Indonesian Sharia Stock Index (ISSI). Like other conventional stocks, ISSI as a capital market can also be influenced by various factors, including inflation, BI interest rates and the USD exchange rate. This study aims to determine the effect of inflation, BI interest rates, and the USD exchange rate on the price of the Indonesian Islamic stock index for the 2019-2022 period. This study uses secondary data from 2019-2022, and the analytical method uses parallel data with multiple regression analysis. The results of this study indicate that inflation has a significant effect on the ISSI index, while BI interest rates and the USD exchange rate have no effect on the ISSI index. However, when analyzed simultaneously, inflation, BI interest rates and the USD exchange rate significantly affect the price of the ISSI index. These findings provide valuable insights for investors and policy makers in understanding the dynamics of the ISSI index and formulating investment strategies in the Indonesian Islamic capital market.